Materials engineering selected, peer reviewed papers from the 2nd International Conference on Materials Engineering (ICMEN 2014), May 17-18, 2014, Nanjing, China - He, Fang (Applied mechanics and materials, 2014)
Collection of selected, peer reviewed papers from the 2nd International Conference on Materials Engineering (ICMEN2014), May 17-18, 2014, Nanjing, China. The 28 papers are grouped as follows: Chapter 1: Function and Electronic Materials,Chapter 2: High Performance Structural Material,Chapter 3: Materials Processing Technology Keyword: Function and Electronic Materials; High Performance Structural Material; Materials Processing Technology Materials scientists and engineers report on recent research into designing new materials, characterizing materials, optimizing manufacturing processes, computer-aided materials calculations, and similar matters. In sections on functional and electronic materials, high-performance structural material, and materials processing technology, 28 papers discuss such topics as the controllable synthesis of mono-dispersed metal oxide nanostructures with a solvothermal route and their catalytic properties, hydration mechanisms of Portland cement with magnesium slag, the mesoscopic simulation analysis of the influence of die wall friction on the compression process of powder particles, and the effect of coiling temperature and cold rolling reduction on the planar anisotropy of low-carbon steel alloyed with titanium. -- Engineering-- Materials science-- Mechanical engineering